Teachers’ strategies to teach writing Explanation texts - Hidayat, Dadan; Jaenudin, Jejen (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
The strategy in teaching is very important for the teacher in teaching writing, especially in teaching writing explanation text. The teacher must have a variety in teaching to help the students study successfully. This research was intended to find out the teaching strategies used by the teachers at SMAN 10 Garut. The purposes of this research are to identify some of the teachers' strategies and techniques used in teaching writing explanations. The data needed is gained through a sample consisting of 4 SMAN 10 Garut (Senior High School) teachers. The teachers are provided with 18 questionnaires. The responses are in the form of Yes, Sometimes, and No to the statements given. Then, the result is formulated by using: = f × 100%. This research used the descriptive method and employed qualitative data. The writer observed the teachers in teaching writing explanation text and using teachers' observation form also. Based on the findings, (61. 11%) of the respondents perceive that various teaching strategies were needed for the students. Based on the writer's interpretation, it is suggested that the teachers practice specific strategies for teaching writing explanations.